Comparative Genomics of Field Isolates of Mycobacterium bovis and M. caprae Provides Evidence for Possible Correlates with Bacterial Viability and Virulence. - José de la Fuente; Iratxe Díez-Delgado; Marinela Contreras; Joaquín Vicente; Alejandro Cabezas-Cruz; Raquel Tobes; Marina Manrique; Vladimir López; Beatriz Romero; Javier Bezos; Lucas Dominguez; Iker A Sevilla; et al. (Public Library of Science (PLoS), 2015)
Mycobacteria of the Mycobacterium tuberculosis complex (MTBC) greatly affect humans and animals worldwide. The life cycle of mycobacteria is complex and the mechanisms resulting in pathogen infection and survival in host cells are not fully understood. Recently, comparative genomics analyses have provided new insights into the evolution and adaptation of the MTBC to survive inside the host. However, most of this information has been obtained using M. tuberculosis but not other members of the MTBC such as M. bovis and M. caprae. In this study, the genome of three M. bovis (MB1, MB3, MB4) and one M. caprae (MB2) field isolates with different lesion score, prevalence and host distribution phenotypes were sequenced. Genome sequence information was used for whole-genome and protein-targeted comparative genomics analysis with the aim of finding correlates with phenotypic variation with potential implications for tuberculosis (TB) disease risk assessment and control. At the whole-genome level the results of the first comparative genomics study of field isolates of M. bovis including M. caprae showed that as previously reported for M. tuberculosis, sequential chromosomal nucleotide substitutions were the main driver of the M. bovis genome evolution. The phylogenetic analysis provided a strong support for the M. bovis/M. caprae clade, but supported M. caprae as a separate species. The comparison of the MB1 and MB4 isolates revealed differences in genome sequence, including gene families that are important for bacterial infection and transmission, thus highlighting differences with functional implications between isolates otherwise classified with the same spoligotype. Strategic protein-targeted analysis using the ESX or type VII secretion system, proteins linking stress response with lipid metabolism, host T cell epitopes of mycobacteria, antigens and peptidoglycan assembly protein identified new genetic markers and candidate vaccine antigens that warrant further study to develop tools to evaluate risks for TB disease caused by M. bovis/M.caprae and for TB control in humans and animals.